#### Answer

$f^{-1}(x)=\frac{x - 7}{-5}$

#### Work Step by Step

f(x) = 7 - 5x
y = 7 - 5x
y - 7 = -5x
$\frac{y - 7}{-5} = x $
$f^{-1}(x)=\frac{x - 7}{-5}$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$f^{-1}(x)=\frac{x - 7}{-5}$

f(x) = 7 - 5x
y = 7 - 5x
y - 7 = -5x
$\frac{y - 7}{-5} = x $
$f^{-1}(x)=\frac{x - 7}{-5}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.